Feasibility and Acceptability of a Multi-Modality Self-Management Intervention for Head and Neck Cancer Caregivers: A Pilot Randomized Trial. (May 2022) - Nightingale, Chandylen; Sterba, Katherine R.; Levine, Beverly; Tooze, Janet A.; Greven, Kathryn; Frizzell, Bart; Hughes, Ryan T.; Snavely, Anna; Lesser, Glenn J.; Norona, Sandra; Pleasant, Katherine; Weaver, Kathryn E.
Background: Head and neck cancer (HNC) patients undergoing radiation therapy (RT) experience significant side effects, presenting challenging care tasks for their informal (unpaid) caregivers. HNC caregivers report low caregiving self-efficacy, high distress, and interest in supportive care interventions. Objective: This randomized pilot trial assessed the feasibility and acceptability of a 6 to 7 week supported self-management intervention (Prepare to Care) offering psychoeducation and stress management skills building for caregivers of patients receiving RT for HNC. Methods: Caregivers were randomized to Prepare to Care or standard of care. Primary feasibility measures included participation and retention percentages. Assessments were completed before the intervention, at intervention completion, and 6-weeks later after intervention completion. Results: Caregivers (N = 38) were predominantly female (88.6%), an average age of 56 years old, and a spouse/partner to the patient (71.4%). Participation percent was 42.2%; retention at intervention conclusion was 80% and 77% at the 6-week follow-up. Quantitative and qualitative results support acceptability, with 64% to 88% reporting each intervention module was helpful (quite a bit or very). Intervention caregivers reported a significantly greater improvement in self-efficacy for progressive muscle relaxation (PMR). Conclusions: Prepare to Care and the randomized pilot trial methods are feasible and acceptable for HNC caregivers of patients receiving RT. A significant treatment effect was observed for self-efficacy for PMR, and findings were in the expected direction regarding improved caregiving self-efficacy. Further research is necessary to determine the efficacy of this intervention with a focus on increased engagement strategies and longer-term outcomes. Trial Registration: NCT03032250